Moral Agency, Rules, and Temporality in People Who Are Diagnosed With Mild Forms of Autism: In Defense of a Sentimentalist View - Coelho, Sara; Bonatti, Sophia Marlene; Doering, Elena; Paskaleva-Yankova, Asena; Stephan, Achim (Frontiers in Psychology, 2022)
The origin of moral agency is a much-debated issue. While rationalists or Kantians have argued that moral agency is rooted in reason, sentimentalists or Humeans have ascribed its origin to empathic feelings. This debate between rationalists and sentimentalists still stands with respect to persons with mental disorders, such as individuals diagnosed with mild forms of Autism Spectrum Disorder (ASD), without intellectual impairment. Individuals with ASD are typically regarded as moral agents, however their ability for empathy remains debated. The goal of this paper is to investigate the mechanisms of moral actions in people with ASD, by finding arguments for the origin of their moral actions, supporting either the sentimentalist or the rationalist view of the dispute. We propose to revisit the debate using Interpretative Phenomenological Analysis to study the autobiographies of individuals with High-Functioning Autism (HFA) and Asperger Syndrome (AS). While conducting the systematic analysis of 10 autobiographies, we re-examined both the rationalist and the sentimentalist positions, considering the links between empathic feelings and moral agency. The investigation of the temporal dimensions of emotional experiences, an aspect overlooked by previous research, indicated that individuals with ASD empathize with others, but in different ways as compared to neurotypicals. A relationship between emotional experience and the type of moral agency exhibited by individuals with forms of ASD was established. As a consequence, our analyses support the sentimentalist stance on moral action.